2020
DOI: 10.1002/ijop.12650
|View full text |Cite
|
Sign up to set email alerts
|

Associations of trait positive emotion regulation with everyday emotions: An experience sampling approach

Abstract: Positive emotion regulation is important for enhancing psychological well‐being. Previous studies have adopted a cross‐sectional design to examine the relationships between positive emotion regulation strategies and psychological functioning. Relatively little is known about the role of positive emotion regulation strategies in positive and negative emotions in everyday life. This study examines associations between perceived capability of savoring and trait positive rumination and everyday emotions. Among 300… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…Within the use of individual strategies, savoring the moment explained the largest amount of variance in the regression analysis. Similar findings on the elevated role of savoring the moment were provided by a study from our colleagues [47] (30) . In the study, the authors found savoring the moment to be the only upregulation strategy that yielded higher pleasant emotions during negatively valenced events.…”
Section: Discussionsupporting
confidence: 86%
“…Within the use of individual strategies, savoring the moment explained the largest amount of variance in the regression analysis. Similar findings on the elevated role of savoring the moment were provided by a study from our colleagues [47] (30) . In the study, the authors found savoring the moment to be the only upregulation strategy that yielded higher pleasant emotions during negatively valenced events.…”
Section: Discussionsupporting
confidence: 86%
“…Savoring correlates with more positive emotion, particularly for individuals with high and moderate (but not low) levels of mindfulness ( Kiken et al, 2017 ). Moreover, savoring correlates with more positive emotion during negative events, and lower negative emotions during positive events, which, overall, may help to amplify net positive emotion ( Ma et al, 2020 ). People with schizophrenia report less savoring than unaffected comparison participants, which may impede the up-regulation of positive affect ( Cassar et al, 2013 ).…”
Section: Psychological Dimensions Relevant To Amotivation and Anhedoniamentioning
confidence: 99%
“…Li, Starr, & Hershenberg (2017) found in a study of young adults that daily rumination effort regarding positive events, also referred to as 'savoring', was negatively associated with daily depressive symptoms. In adults, Ma, Bryant, & Hou (2020) also found that higher positive trait rumination was associated with greater positive affect during positive events. Furthermore, in adulthood, a dispositional tendency to think about one's positive experiences and allocate attention to them has been associated with higher life-satisfaction and lower depression (Bryant, 2003).…”
Section: Positive Emotions and Psychopathologymentioning
confidence: 78%